A Four-MicroRNA Panel in Peripheral Blood Identified as an Early Biomarker to Diagnose Acute Myocardial Infarction - Chen, Liang; Bai, Jie; Liu, Jun; Lu, Huihe; Zheng, Koulong (Frontiers in Physiology, 2021)
Objective: This study aimed to evaluate suitable circulating microRNAs (miRNAs) as diagnostic biomarkers of acute myocardial infarction (AMI). Methods: Patients with AMI were enrolled as study participants. All patients with AMI coming from the Second Affiliated Hospital of Nantong University between October 1, 2017 and May 31, 2019 were screened. At the same time, 80 patients with coronary angiographic stenosis <50% during the same period were selected as the control group. Peripheral blood samples were collected at different time points (0, 6, 12, and 24 h after disease onset) to detect the expression of a previously identified promising four-microRNA panel. The expression levels of miRNAs were tested by real-time polymerase chain reaction (RT-PCR), and the receiver operating characteristic curve (ROC) was used to analyze the diagnostic value of circulating miRNAs. Results: Based on the inclusion and exclusion criteria, 80 patients with AMI and 80 controls were enrolled in this study. The expression of circulating miR-1291, miR-217, miR-455-3p, and miR-566 was significantly downregulated in patients with AMI compared with controls. The area under the ROC curve (AUC) of circulating miR-1291, miR-217, miR-455-3p, and miR-566 were 0.82, 0.79, 0.82, and 0.83, respectively. The AUC of these four miRNAs was 0.87 with 83% sensitivity and 87% specificity. The expression peaks of these four miRNAs occurred earlier than those of cardiac troponin I (cTnI) and creatine kinase-MB (CK-MB). Furthermore, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that the targets of these four miRNAs were significantly enriched in several signaling pathways associated with AMI progression. Conclusion: Circulating miR-1291, miR-217, miR-455-3p, and miR-566 expression levels were significantly lower in patients with AMI; and combined, this panel of four miRNAs acted as a novel and potential early diagnostic biomarker of AMI.